Cyclin-dependent kinase 6 (CDK6) as a potent regulator of the ovarian primordial-to-primary follicle transition - Ataei-Nazari, S.; Amoushahi, M.; Madsen, JF.; Jensen, J.; Heuck, A.; Mohammadi-Sangcheshmeh, A.; Lykke-Hartmann, K. (Frontiers in Cell and Developmental Biology, 2022)
Introduction: Ovarian follicle development requires tight coordination between several factors to initiate folliculogenesis to generate a mature and fertile egg. Studies have shown that cell cycle factors might contribute to follicle development, hover specific knowledge on individual CDKs and follicle activation has not been investigated. Among cell cycle regulators, CDK6 is a key player through binding to cyclin D resulting DNA synthesis and genome duplication. Interestingly, the CDK6 gene is differentially expressed in oocytes and granulosa cells from human primordial and primary follicles, which suggest a potential role of CDK6 in the primordial-to-primary transition. In this study, we investigated the potential regulatory role of CDK6 in progression of primordial to primary follicle transition using BSJ-03-123 (BSJ), a CDK6-specific degrader. Methods: In mouse ovarian in vitro culture, BSJ reduced the activation of primordial follicles, and reduced follicle development. As a next step, we examined the egg maturation read-out and found that BSJ-treated follicles matured to competent MII eggs with resumption of first meiosis, comparable with the control group. Results: Noteworthy, it appears that inhibition of CDK6 did increase number of apotoptic cells, articular in the granulosa cells, but had no impact on ROS level of cultured ovaries compared to control group, indicating that the cells were not stressed. Oocyte quality thus appeared safe. Discussion: The results of this study indicate that CDK6 plays a role in the primordial-to-primary transition, suggesting that cell cycle regulation is an essential part of ovarian follicle development.